2009
DOI: 10.1007/s10096-009-0720-x
|View full text |Cite
|
Sign up to set email alerts
|

New 16-plex PCR method for rapid detection of diarrheagenic Escherichia coli directly from stool samples

Abstract: A rapid 16-plex polymerase chain reaction (PCR) suitable for routine diagnostics of diarrheagenic Escherichia coli (EHEC, EIEC, EAEC, ETEC, and EPEC) was developed, validated with control strains, and tested with 250 diarrhoeal stool samples. The specificity was 100% when tested with 289 control bacterial strains, and the analytical sensitivity of automated DNA extraction directly from stool samples was made by boiling the bacterial culture (10(4)-10(5) colony forming units/ml). The assay design starting direc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
70
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(72 citation statements)
references
References 22 publications
1
70
1
Order By: Relevance
“…[26][27][28][29] The increasing o pathogenic and commensal ESBL-producing E. coli strains are originated from different sources (such as human, food, and animal) and the dissemination of antibiotic resistance among other members of Enterobacteriaceae is a worldwide problem in the control and treatment of infections in human and animals. 20,[30][31][32][33][34] Moreover, some studies have shown that infections caused by ESBL-producing bacteria leads to the increase in the economic costs of infections treatment and the morbidity and mortality of diseases.…”
Section: Discussionmentioning
confidence: 99%
“…[26][27][28][29] The increasing o pathogenic and commensal ESBL-producing E. coli strains are originated from different sources (such as human, food, and animal) and the dissemination of antibiotic resistance among other members of Enterobacteriaceae is a worldwide problem in the control and treatment of infections in human and animals. 20,[30][31][32][33][34] Moreover, some studies have shown that infections caused by ESBL-producing bacteria leads to the increase in the economic costs of infections treatment and the morbidity and mortality of diseases.…”
Section: Discussionmentioning
confidence: 99%
“…16-plex PCR assay:The presence of STEC, EPEC, ETEC, EIEC and EAEC in human diarrhoeal stoolssamples was detected by 16-plex PCR for the genes uidA, pic, bfp, invE, hlyA, elt, ent, escV, eaeA, ipaH, aggR, stx1, stx2, estIa, estIband astA. The primers and PCR conditions were as previously described [10]. The nucleotide sequences and predicted sizes of the amplified products for the specific oligonucleotide primers used in this study are shown in Table 1.…”
Section: Cultivation Samplesmentioning
confidence: 99%
“…Therefore, rapid and reliable detection of STEC isolates in food and clinical samples is required. The direct molecular detection of Shiga toxin (Stx1 or Stx2) genes alone or in combination with other genes coding for major STEC virulence factors by nucleic acid-based techniques is known to be highly sensitive and specific in STEC detection (1,2,10,25). Major disadvantages of these assays are, however, the labor-intensive sample preparation and the increase of the costs when used only for screening purposes.…”
mentioning
confidence: 99%